2022
DOI: 10.3389/fmed.2022.938536
|View full text |Cite
|
Sign up to set email alerts
|

A multicenter prospective cohort study of cardiac ultrasound phenotypes in patients with sepsis: Study protocol for a multicenter prospective cohort trial

Abstract: BackgroundSepsis-induced cardiomyopathy significantly increased the mortality of patients with sepsis. The diagnostic criteria for septic cardiomyopathy has not been unified, which brings serious difficulties to clinical treatment. This study aimed to provide evidence for the early identification and intervention in patients with sepsis by clarifying the relationship between the ultrasound phenotype of septic cardiomyopathy and the prognosis of patients with sepsis.MethodsThis was a multicenter, prospective co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…It turns out that, by recognizing and differentiating early septic patients among different hemodynamic phenotypes, hemodynamic support, such as with vasopressors, could be somehow individualized and inotropes infusion and fluid resuscitation could be tailored to the need of each specific phenotype. Currently, there is at least one on-going clinical trial that investigates whether there is an association between the phenotype of septic cardiomyopathy, based on ultrasound characteristics, and the outcome of sepsis [ 95 ]. In addition, ANDROMEDA-2 study investigators seek to determine whether in early septic shock, i.e., <4 h of diagnosis, a peripheral perfusion-guided strategy compared to standard care, applied to different patient phenotypes identified by different clinical and hemodynamic criteria, could improve their outcome (mortality, duration of organ support and hospital length of stay) [ 96 ].…”
Section: Hemodynamic Phenotyping and Sepsismentioning
confidence: 99%
“…It turns out that, by recognizing and differentiating early septic patients among different hemodynamic phenotypes, hemodynamic support, such as with vasopressors, could be somehow individualized and inotropes infusion and fluid resuscitation could be tailored to the need of each specific phenotype. Currently, there is at least one on-going clinical trial that investigates whether there is an association between the phenotype of septic cardiomyopathy, based on ultrasound characteristics, and the outcome of sepsis [ 95 ]. In addition, ANDROMEDA-2 study investigators seek to determine whether in early septic shock, i.e., <4 h of diagnosis, a peripheral perfusion-guided strategy compared to standard care, applied to different patient phenotypes identified by different clinical and hemodynamic criteria, could improve their outcome (mortality, duration of organ support and hospital length of stay) [ 96 ].…”
Section: Hemodynamic Phenotyping and Sepsismentioning
confidence: 99%
“…Emerging perspectives on precision medicine have broadened our understanding of sepsis to sepsis-endotypes or sepsis-phenotypes [19]. Potentially, there is a group of patients in whom the cardiovascular system gets affected predominantly [20,21]. A recent study demonstrated that in patients with sepsis-induced cardiomyopathy, veno-arterial ECMO might offer a better outcome [20].…”
mentioning
confidence: 99%